Lifestyle habits of 12, 800 IVF patients: Prevalence of negative lifestyle behaviors, and impact of region and insurance coverage. (2nd October 2015) - Domar, Alice D.; Rooney, Kristin L.; Milstein, Melissa; Conboy, Lisa
Abstract : Lifestyle habits of women undergoing in vitro fertilization (IVF) treatment are largely unknown. Therefore, this prospective study aimed to determine the prevalence of negative lifestyle habits in women undergoing IVF and determine if habits are related to the region in the United States and/or by mandated insurance coverage. A total of 12, 811 ART patients were surveyed in infertility clinics throughout the US. They took an online questionnaire added to the patient portal of electronic medical record eIVF, a fertility-specific electronic health record. Of the women surveyed, 17–23% of patients drank alcohol, 2–7% smoked, 62–68% drank caffeine, < 1% used recreational drugs, and 47–62% exercised during their IVF treatment. There were a few statistically significant regional differences in health habits ( p < 0.001) but there were no differences in health habits between women who resided in a state with mandated insurance coverage versus those without insurance coverage. This is the first prospective assessment of lifestyle habits across regions in the USA and by insurance coverage. The study concluded that women undergoing IVF engage in behaviors which may negatively impact their cycle. Women in certain parts of the US had significantly worse habits than other regions, but the availability of mandated insurance coverage did not impact health habits.